THE IMPORTANCE OF AGRO-SERVICES IN ECONOMIC DEVELOPMENT (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Agro-services play a pivotal role in the economic development of countries by enhancing agricultural productivity, promoting technological innovation, and supporting rural livelihoods. These services encompass a range of activities, including the provision of quality inputs, mechanization support, extension services, market information, and financial assistance, all of which are essential for increasing efficiency and profitability in agriculture. By improving resource utilization and facilitating access to modern agricultural techniques, agro-services contribute not only to higher crop yields and food security but also to employment generation and poverty reduction. The integration of agro-services with broader economic policies ensures sustainable growth, strengthens the agribusiness sector, and stimulates related industries, thereby fostering overall economic development. Moreover, agro-services enhance farmers’ resilience to environmental and market risks, support value chain development, and encourage private sector participation, which collectively drive economic diversification and inclusive growth. Understanding the importance of agro-services is thus crucial for policymakers, development agencies, and stakeholders aiming to achieve sustainable agricultural development and long-term economic progress.